Two new strains of Streptomyces with metabolic potential for biological control of pear black spot disease - Yi-Huang Chen; Jia-Xing Zhang; Yan Min; Yang Liu; Jian-Ming Wang; Lin-Quan Bai; Xiao-Xia Luo (BMC Microbiology)
Abstract Background Pear black spot is caused by Alternaria tenuissima. It is one of the diseases of concern limiting pear production worldwide. Existing cultivation methods and fungicides are not sufficient to control early blight. Therefore, the aim of this study was to isolate and characterize two strains of Streptomyces and evaluate their potential for biological control of crop diseases caused by Alternaria tenuissima while promoting plant growth. It enriches the resources of biocontrol strains. Methods In this study, the genetic background of the strain was elucidated through 16 S rRNA gene analysis and multiphase taxonomic identification methods. The metabolic potential of the strain was assessed using a variety of approaches, including antiSMASH, COG, and KEGG databases, RGI tools, as well as the scanning of CAZY and plant-promoting genes. The biocontrol potential of the strain was further substantiated through a combination of plate experiments, gene cluster biopathway resolution and mass spectrometry validation of metabolites. Finally, the biocontrol efficacy of the strain was confirmed through fruit control experiments. Results The study identified the potential new species status of the strains. Strain TRM 76130 exhibited a gene size of 5.94 Mbp and a G + C content of 73.65%, while strain TRM 76172 had a gene size of 8.30 Mbp and a G + C content of 71.38%. Both strains contained genes related to amino acid transport and metabolism, along with several CAZY genes and 19 plant growth factors. The resistance genes of strain TRM 76172 were classified as macrolides, and genomic prediction revealed the biosynthetic pathway of the active compound Candidin. Mass spectrometry analysis indicated that strains TRM 76172 and TRM 76130 contained the active compounds amphotericin A and daptomycin, respectively. The pear assays demonstrated that both strains of Streptomyces were capable of reducing the symptoms of pear black spot. Conclusion The present study concludes that strains TRM76172 and TRM76130 possess significant potential to control Alternaria tenuissima and promote plant growth, thereby enriching the biocontrol fungal library.